BUDGET DEFICIT CAUSES INFLATION? APPLICATION TO PORTUGAL - Rosa, Agostinho Silvestre (Análise Econômica, 2017)
The analysis of Portuguese inflation, based on annual data from 1961 to 2012, using the Johansen Method, allows us to conclude that variation in Portuguese inflation is determined essentially by foreign inflation and by variation in the effective exchange rate, but the lagged variation of budget deficit seems to causes variation of inflation in the studied period. In the long run there are two long-run relationships. Both the inflation rate and the wage inflation rate relate positively with the General Government Balance in percentage of GDP, negatively with the exchange rate index, positively with the foreign inflation index and negatively with the trend. In the short run the variation of the inflation rate relates positively with foreign inflation (or its variation) and the variation in the effective exchange rate, relates negatively with the error correction mechanism, so there is a significant response to the equilibrium error between inflation rate and its determinants. In addition to this adjustment, the inflation rate responds positively and significantly to the lagged variation of the budget deficit, as expected.